2003
DOI: 10.1002/ajmg.a.20555
|View full text |Cite
|
Sign up to set email alerts
|

A novel type of autosomal recessive syndactyly: Clinical and molecular studies in a family of Pakistani origin

Abstract: Non-syndromic syndactylies have been classified into five major types (I-V), all showing autosomal dominant mode of inheritance. Later, the classification was extended and three additional variants (VI-VIII) were defined. Type VII, the Cenani-Lenz syndactyly, is the only non-syndromic, autosomal recessive type. It is characterized by fusion of all phalanges with metacarpal synostosis, dislocated and dysplastic carpals and infrequently, radio-ulnar fusion. Here, we present a Pakistani family with a novel non-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Interestingly, the limb phenotype in the absence of Epfn is comparable to the recently identified human mesoaxial synostotic syndactyly (MSSD, type IX syndactyly) (Malik et al, 2004; 2005) although the specific digits affected differs between human and mouse. This type of syndactyly is characterized by the mesoaxial reduction of fingers due to bony fusion of the third and fourth metacarpals bearing single phalanges.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly, the limb phenotype in the absence of Epfn is comparable to the recently identified human mesoaxial synostotic syndactyly (MSSD, type IX syndactyly) (Malik et al, 2004; 2005) although the specific digits affected differs between human and mouse. This type of syndactyly is characterized by the mesoaxial reduction of fingers due to bony fusion of the third and fourth metacarpals bearing single phalanges.…”
Section: Discussionsupporting
confidence: 62%
“…Malik et al, [124] found similar findings in another family, with an autosomal recessive trait, and ruled out genome candidates at 2q34-q36, 2q31, and 6q22-q23. The previous family had had HOXD13 and the genome associated with 2q31 disproved as causative by Percin et al, Merging the two families into one study has revealed a likelihood of a causal gene being mapped to chromosome 17p13.3 [125].…”
Section: Syndactyly: the Genetic Search And A Problem For Clinical CLmentioning
confidence: 65%
“…Malik et al (2005) described the mapping of a locus for an autosomal recessive form of mesoaxial synostotic syndactyly, MSSD-type IX with phalangeal reduction to chromosome region 17p13.3. (Malik et al 2004(Malik et al , 2005. The SHFLD locus mapped by us is fully enclosed in the MSSDtype IX syndactyly locus.…”
Section: Resultsmentioning
confidence: 99%